Fibroadenoma with Foci of Infiltrating Ductal Carcinoma - Jahan, Fauzia; Ghosh, PK; Rahman, Saidur; Khanam, Rehana (Journal of Medicine, 2012)
Fibroadenoma is a biphasic tumor of breast with stromal and epithelial components. It is a very common benign tumor among young female. Malignant transformation in a fibroadenoma is uncommon. We report a case of an elderly patient with bilateral fibroadenomas harboring foci of invasive ductal carcinoma. The intent of this presentation is to increase general awareness as to the existence of carcinomas arising in fibroadenomas and also to actively discourage the practice of rendering gross pathological diagnoses of fibroadenomas. DOI: http://dx.doi.org/10.3329/jom.v13i1.10088 JOM 2012; 13(1): 115-117